Development and application of an indirect enzyme-linked immunosorbent assay for serological survey of Japanese encephalitis virus infection in dogs - Shimoda, Hiroshi; Inthong, Natnaree; Noguchi, Keita; Terada, Yutaka; Nagao, Yumiko; Shimojima, Masayuki; Takasaki, Tomohiko; Rerkamnuaychoke, Worawut; Maeda, Ken (Journal of virological methods, 2013)
► A simple method for detecting JEV antibodies in sera from dogs was developed. ► This ELISA is useful for assessment of the human risk of JEV infection. ► Both ELISA and virus neutralization should be used for serological surveys of JEV. Japanese encephalitis virus (JEV) causes serious acute encephalitis in humans and horses. Although dogs are good sentinels for assessing the risk of JEV infection to humans, a virus neutralization test has been the only method available for measuring the levels of JEV antibody in dogs. In this study, an indirect enzyme-linked immunosorbent assay (ELISA) using purified viral particles as an antigen, was developed for serological survey of JEV infection in dogs. In dogs inoculated experimentally with JEV, the ELISA detected anti-JEV IgM 3 days after infection, with IgM levels peaking 7 days after infection. Anti-JEV IgG was detected 14 days after infection and peaked on 21–28 days after infection. Virus neutralization titers correlated with anti-JEV immunoglobulins measured by the ELISA. To test the utility of the new assay, the seroprevalence of JEV infection among 102 dogs in Kyushu, Japan, was examined by IgG ELISA and by virus neutralization. The correlation coefficient between the IgG ELISA and virus neutralization was 0.813 (p<0.001); comparison of the IgG ELISA and virus neutralization showed a sensitivity and specificity of 82% and 98%, respectively. The IgG ELISA was used to survey dogs in Bangkok, Thailand and 51% of these dogs were found seropositive for JEV. These data suggest that in the capital city of Thailand, the risk of infection with JEV remains high.